2019
DOI: 10.1055/a-0865-1842
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasound Elastography in the Detection of Fibrotic Bowel Strictures in Patients with Crohn’s Disease: Systematic Review and Meta-Analysis

Abstract: Purpose To perform a systematic review with meta-analysis to assess whether ultrasound elastography can have a diagnostic role in detecting fibrotic bowel strictures in patients with Crohn’s disease. Materials and Methods MEDLINE via the PubMed, Ovid Embase, Scopus and Cochrane Library databases, and abstracts of international conference proceedings were searched up to March 31, 2018. Studies were included if they assessed the performance of abdominal ultrasound elastography in detecting fibrotic bow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Three studies used strain elastography and showed that the strain ratio was higher in strictures with fibrosis compared to strictures without fibrosis (p 0.05). Similar results were found by the other three studies that used SWE, where the strain value was statistically higher in fibrotic stenosis (p 0.08) (Vestito et al, 2019).…”
Section: Sonoelastographysupporting
confidence: 88%
See 1 more Smart Citation
“…Three studies used strain elastography and showed that the strain ratio was higher in strictures with fibrosis compared to strictures without fibrosis (p 0.05). Similar results were found by the other three studies that used SWE, where the strain value was statistically higher in fibrotic stenosis (p 0.08) (Vestito et al, 2019).…”
Section: Sonoelastographysupporting
confidence: 88%
“…Conventionally, the blue or red color means hard or soft tissue, respectively. The system gives either a qualitative and subjective assessment of the stiffness by examining the colors, and a quantitative estimation of the stiffness, by comparing the value within a region of interest in the wall with a similar one outside of the wall, usually taken from the softer tissue around (Stidham et al, 2011;Lu et al, 2019;Vestito et al, 2019). On the contrary, the SWE is a system that directly calculates the elasticity in kPascal thanks to the diffusion of the beam within the tissue in specific regions of interest, without the necessity to pressurize repeatedly the abdomen (Vestito et al, 2019).…”
Section: Sonoelastographymentioning
confidence: 99%
“…Given the substantial number of studies comparing MRE imaging with IUS imaging, our study did not aim to compare different radiologic modalities in a strictly controlled population, but to determine the yield of ultrasonographic examination performed using a portable system in a real-life setting. The portable ultrasonography system used in this study lacked elastography and contrast-enhanced ultrasonography modalities, both of which can increase the diagnostic capability of ultrasonographic imaging [ 25 , 26 ]. The addition of these modalities into portable systems may enhance the system’s accuracy in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Chen [23] looked at the distinction of intestinal fibrosis from inflammation in Crohn's disease (CD)-associated strictures, as presented by Vestito [24] in a systematic review with meta-analysis to assess whether ultrasound elastography can have a diagnostic role in detecting fibrotic bowel strictures in patients with Crohn's disease. The study included consecutive CD patients with ileal/ileocolonic strictures who had shear wave elastography (SWE) within 1 week of surgical resection.…”
Section: Ultrasound Elastography To Detect Fibrotic Bowel Strictures In Crohn's Diseasementioning
confidence: 99%